Targeted enhancement of bacteriophage activity against antibiotic-resistant Staphylococcus aureus biofilms through an evolutionary assay - Ponce Benavente, Luis; Wagemans, Jeroen; Hinkel, Dennis; Aguerri Lajusticia, Alba; Lavigne, Rob; Trampuz, Andrej; Gonzalez Moreno, Mercedes (Frontiers in Microbiology, 2024)
Staphylococcus aureus´ biofilm-forming ability and rapid resistance development pose a significant challenge to successful treatment, particularly in postoperative complications, emphasizing the need for enhanced therapeutic strategies. Bacteriophage (phage) therapy has reemerged as a promising and safe option to combat multidrug-resistant bacteria. However, questions regarding the efficacy of phages against biofilms and the development of phage resistance require further evaluation. Expanding on the adaptable and evolutionary characteristics of phages, we introduce an evolutionary approach to enhance the activity of S. aureus phages against biofilms. Unlike other in vitro directed evolution methods performed in planktonic cultures, we employed pre-stablished biofilms to do a serial-passage assay to evolve phages monitored by real-time isothermal microcalorimetry (IMC). The evolved phages demonstrated an expanded host range, with the CUB_MRSA-COL_R9 phage infecting 83% of strains in the collection (n=72), surpassing the ISP phage, which represented the widest host range (44%) among the ancestral phages. In terms of antimicrobial efficacy, IMC data revealed superior suppression of bacterial growth by the evolved phages compared to the ancestral CUB-M and/or ISP phages against the respective bacterial strain. The phage cocktail exhibited higher efficacy, achieving over 90% suppression relative to the growth control even after 72 hours of monitoring. Biofilm cell-counts, determined by RT-qPCR, confirmed the enhanced antibiofilm performance of evolved phages with no biofilm regrowth up to 48 hours in treated MRSA15 and MRSA-COL strains. Overall, our results underscore the potential of biofilm-adapted phage cocktails to improve clinical outcomes in biofilm-associated infections, minimizing the emergence of resistance and lowering the risk of infection relapse. However, further investigation is necessary to evaluate the translatability of our results from in vitro to in vivo models, especially in the context of combination therapy with the current standard of care treatment.